Collision and grounding of ships and offshore structures : proceedings of the 6th International Conference on Collision and Grounding of Ships and Offshore Structures, ICCGS, Trondheim, Norway, 17-19 June 2013 - Amdahl, Jørgan, 1951-; Ehlers, Sören (College teacher); Leira, Bernt J. (CRC Press/Balkema, 2013)
Collision and Grounding of Ships and Offshore Structures contains the latest research results and innovations presented at the 6th International Conference on Collision and Grounding of Ships and Offshore Structures (Trondheim, Norway, 17-19 June 2013). The book comprises contributions made in the field of numerical and analytical analysis of collision and grounding consequences for ships and offshore structures in various scenarios, such as narrow passageways and arctic conditions including accidental ice impact. A wide range of topics is covered: - Recent large-scale collision experiments - I.